"Evil" intentions: Examining the relationship between the Dark Tetrad and victim selection based on nonverbal gait cues. (1st February 2019) - Ritchie, Mary B.; Blais, Julie; Forth, Adelle E.
Abstract: The current study sought to examine the association between the Dark Tetrad traits and accuracy in assessing a target's vulnerability using nonverbal gait cues. In a sample of 126 undergraduates, accuracy was positively associated with psychopathy, Machiavellianism, and everyday sadism, while narcissism was unrelated to accuracy. A hierarchical linear regression analysis also suggested that there is considerable overlap between these constructs, as Machiavellianism and everyday sadism did not add incrementally to the prediction of accuracy over and above psychopathy. Overall, this study provides support for previous research associating psychopathy with accuracy in perceiving other's vulnerability based on gait cues and raises questions about the construct validity of the Dark Tetrad. While the fault of victimization lies solely on the perpetrator, it is important to explore whether vulnerability cues can be modified to reduce predatory behavior. Highlights: Psychopathy associated with accuracy in perceiving vulnerability to victimization Considerable overlap between psychopathy, Machiavellianism, and everyday sadism No association between narcissism and accuracy in perceiving vulnerability Factor 2 psychopathy predicts accuracy over and above Machiavellianism and sadism. Presence of gait cues contributes to accuracy in perceiving vulnerability.